Garbage Disposal Information System Using Internet of Things - Timbo Faritcan Siallagan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The waste management carried out by the Puri Panji Kencana Residential and Buana Grand Subang Housing Communities, West Java, is related to the community's perception of waste and the condition of the area where they live. Therefore, this study aims to determine the public's perception of waste, the waste management system, and the public's perception of the effectiveness of waste management in areas with different topography. This study used a survey method with data collection techniques in the form of distributing questionnaires to the respondents. The sampling technique used in this study was quota sampling by selecting 90 respondents in the three research areas. The analysis technique used is the crosstabs and chi square techniques obtained using the SPSS program. The results of this study indicate that people in the three regions with different topography have a positive perception of waste and regard waste as items that can still be recycled. There are differences in waste management in the three research locations, the flatter an area, the better the level of waste management. The effectiveness of waste management according to public perceptions from various aspects is more felt by people in flat and slightly wavy topography.